A systematic review of paper- based and digitalboard games for collaborative science learning - Mohd Kamal, Othman; Rahimah, Mat; Kah Ching, Sim (John Wiley & Sons Ltd on behalf of British Educational Research, 2025)
This study reviews the literature on board games for collaborative learning in science education, analysing 76 articles from 2000 to 2024. It examines research methodologies, data collection tools, sample sizes, and data analysis methods, focusing on subject areas and types of board games used. Key findings reveal a predominance of physical (paper-based) board games. Research methodologies were primarily quantitative, with descriptive analysis being the most common approach, typically employing varied sample sizes (median 48.5 participants). Evidence suggests that board games can enhance scientific knowledge acquisition, improve student engagement, and foster collaborative skills. However, the review identifies critical limitations in the existing literature, including a prevalence of small sample sizes, a lack of long-term effectiveness studies, and insufficient focus on specific game mechanisms. Future research should prioritise investigating game mechanisms, explicitly measuring collaborative learning outcomes, improving methodological rigour, and assessing long-term impacts on knowledge retention.